Flexible silicon semiconductor in IOT - Sachin Mathew John (Nanyang Technological University, 2023)
Semiconductor Nanomembranes are the basic building blocks of modern technology hence achieving maximum efficiency and performance is crucial in the advancements of technology. Silicon’s exceptional flexibility, durability and inexpensive costs enables it to be ideal in the manufacturing of semiconductors. Hence, this report will be based on the study of flexible Silicon Nanomembranes, the transfer printing process using Polydimethylsiloxane and Polyethylene terephthalate, the fabrication of Silicon materials using positive and negative photoresist and lastly, characterization based on Ramen Spectroscopy and Current - Voltage Measurement tests.